(3+1)-dimensional Sasa-Satsuma equation under the effect of group velocity dispersion, self-frequency shift and self-steepening - Ozisik, Muslum; Secer, Aydin; Bayram, Mustafa (ELSEVIER GMBH, 2023)
Purpose: The aim of this study is to examine the effects of the coefficients of group velocity dispersion, self-frequency shift and self-steepening terms on the optical solitons of the (3+1) -dimensional Sasa-Satsuma equation which is important for modeling many physical events and it has recently been introduced to the literature.Methodology: To get desired results we have used the solution approach as following. The first step is defining the wave transform and applying it to the nonlinear partial differential equation (NLPDE). Then we have obtained the ordinary differential equation (ODE). Afterwards it is introduced and applied the new Kudryashov method (nKM) and unified Riccati equation expansion method (UREEM) to obtain the algebraic equation system. Finally, by determining the parameters from the solution of algebraic system we have substituted them in the solution function.Findings: By using the solution function we have obtained interesting soliton graphics un-der different parameter values. In addition to the basic solitons of the (3+1)-dimensional Sasa-Satsuma equation (SSE), V-shaped and periodic singular type solitons have also been obtained.Originality: The findings of the soliton behaviors under the parameter values effect has not been studied before. The results presented in the article are reported for the first time.
Keywords: Third order dispersion; Optical soliton; Influence of the parameter; The new Kudryashov; Unified Riccati equation expansion; NONLINEAR SCHRODINGERS EQUATION; OPTICAL SOLITON PERTURBATION; INVERSE SCATTERING TRANSFORM; PORSEZIAN-DANIEL MODEL; KUNDU-ECKHAUS EQUATION; CONSERVATION-LAWS; FIBERS; COUPLE; Optics